Inhibition of lncRNA Dlx6os1 decreases cell proliferation and fibrosis and increases cell apoptosis in diabetic nephropathy - Cheng, Jie (Int J Clin Exp Pathol, 2018)
This study aimed to investigate the effect of the long non-coding RNA (lncRNA) Dlx6os1 inhibitor on cell proliferation, apoptosis and fibrosis in mouse mesangial cells (MMCs) under high glucose (HG) conditions. SV40 MES13 cells were cultured under 30 mmol/L glucose (HG group), 5.6 mmol/L glucose (normal glucose group, NG group) and 5.6 mmol/L glucose plus 24.4 mmol/L 3-O-methyl-D-glucose (osmotic control group, OC group), and expressions of lncRNA Dlx6os1, Gm13730, Rdh9, Chrm2 and Bex1 were determined by qPCR. NC-inhibitor plasmids and lncRNA Dlx6os1 inhibitor plasmids were transfected into SV40 MES13 cells cultured under HG conditions, and cell proliferation (at 0 h, 24 h, 48 h and 72 h), and the apoptosis rate (at 72 h), proteins and mRNAs expressions for proliferation and fibrosis markers (at 72 h) were detected by CCK-8, AV-PI, Western blot and qPCR assays, respectively. LncRNA Dlx6os1 was increased in the HG group compared with the OC and NG groups, while no difference of lncRNA Gm13730, Rdh9, Chrm2 or Bex1 was discovered among the three groups. The lncRNA Dlx6os1 inhibitor decreased cell proliferation at 24 h, 48 h and 72 h post plasmids transfection by the CCK-8 assay and reduced the expressions of Cyclin D1 and proliferating cell nuclear antigen (PCNA) mRNA and protein expressions compared with the NC-inhibitor. The cell apoptosis rate at 72 h increased compared with the NC-inhibitor. In addition, protein and mRNA expressions of markers for cell fibrosis (fibronectin and collagen I) were all decreased in the lncRNA Dlx6os1-inhibitor group compared to the NC-inhibitor group. In conclusion, inhibition of lncRNA Dlx6os1 decreases cell proliferation and fibrosis and increases cell apoptosis in diabetic nephropathy.